IMPROVEMENT OF PEDAGOGICAL TECHNOLOGIES AND PEDAGOGICAL SKILLS - Mambekova Shaxnoza Kudiyarbekovna (International Scientific and Current Research Conferences, 2023)
The contemporary educational landscape is witnessing a paradigm shift, propelled by the integration of pedagogical technologies and the emphasis on enhancing pedagogical skills. This thesis delves into the critical role of pedagogical technologies in modern education and the concurrent necessity to augment pedagogical skills for effective teaching practices.The study begins by exploring the historical evolution of pedagogical methodologies, tracing their adaptation to the digital era. It investigates various pedagogical technologies, ranging from interactive learning platforms to adaptive educational tools, and examines their impact on teaching methodologies and learning outcomes.